Guardian of the Faith - Grajewski, Andrzej (Studia Theologica Varsaviensia, 2019)
The assistance for the repressed Church in the Soviet Union was a very important issue in the service of Primate of Poland Cardinal Stefan Wyszyński. The activity of priest Primate’s in this field was conducted within several areas: covert holy orders and bishop consecrations, collecting and transferring information to the Holy See about the situation of the Church in the Soviet Union and permanent attempts with subsequent popes and their closest associates to request them so that this area would not stop functioning in the awareness of the Church and its highest shepherds. The confidential consecration of bishop Jan Cieński with the entitlements of an auxiliary bishop for archdiocese of Lviv, which took place in June 1967 was particularly significant. He was the only bishop of Latin rite in the Ukraine until the collapse of the Soviet Union. Priest Primate conducted his mission with the use of extraordinary entitlements granted to him in 1957 by the Pope Pius XII, and subsequently prolonged by next popes, until John Paul II. These entitlements mainly concerned the Ukraine and Belarus, and Lithuania, in special cases. Cardinal Wyszyński was actively participating in the debate on the issue of the eastern policy of the Holy See. He critically evaluated some advances in diplomacy of the Holy See, accusing them of insufficient demand for religious freedom for Christians in the East.